(untitled) (International Journal of Engineering and Computer Science, 2019)
In the present scenario the health is the prime concern for every of us. Due to the increase in pollution and the other contaminants in environmental atmosphere the chances of getting a disease is became a common factor. No, doubt we are very cautious to prevent ourselves but still due to because of busy schedule we can’t able to take a proper precaution. Hence the medical science in association with modern technology and with the contribution of AI, has invented various gadgets using which we can take a precaution at earlier stages of disease. These devices are using the secure mode of data transmission for transferring the data in private mode. Here in this paper we are going to discuss the various aspect of medically analysis and detection of disease in Health care.